IMPROVING TEACHER PERFORMANCE THROUGH IMPROVING THE EFFECTIVENESS OF TRANSFORMATIONAL LEADERSHIP AND CLINICAL SUPERVISION OF SCHOOL HEADS (RESEARCH ON TEACHERS OF PRIVATE SMP KOTA DEPOK, WEST JAVA) - EE Junaedi Sastradiharja; Daningsih Kurniasari (STIT AL-AMIN KREO TANGERANG, 2020)
The teacher holds the functions and roles that are very important in achieving the success of the education and learning process. The function and role of the teacher cannot be replaced by technological advances in the form of any sophisticated media. Psychologically-pedagogically the teacher in carrying out his teacher's tasks not only plays a role to transfer knowledge to students, but also shapes character and nature through developing the desired personality and values lovingly. Morally, the teacher as an educator also has a role in inheriting the values and virtues of life to become a guide for students in living their lives in the future. Inheritance and the inculcation of life values are not only taught verbally in the same direction as can be obtained through electronic learning media, but must be well communicated not only through rhetorical lectures and speeches, the most meaningful must be through examples and real life attitudes. Given the strategic function and role of teachers, teacher performance must continue to be improved so that teachers are able to become educational resources that determine the success of education and learning. Teacher performance is the key to success in improving the quality of education, because teachers are at the central point of every reform effort directed at qualitative changes in education and learning in a more advanced direction. Improving teacher performance can be done, among others, by increasing the effectiveness of transformational leadership and clinical supervision of school principals, because school principals are the central figure who has authority in teacher empowerment.